Utilization Of Automation In Providing Flight Information At The Aerodrome Control Tower Unit - Mutiara Ayu Umi Hanifah; Djoko Jatmoko; Umi Salamah (Yayasan Sinergi Multidimensi Kreatif, 2024)
This journal discusses the analysis of automation needs for the Air Traffic Controller (ATC) in the Aerodrome Control Tower unit in providing information to improve air traffic services for aerodrome traffic. The research was conducted by analyzing data and information obtained from ATC and air operators. Besides that, it also analyzes problems in the field that hinder the efficiency of the process of providing information from ATC to air operators (pilots). The analytical method used is SWOT analysis by considering internal and external factors to develop an effective strategy. The results of the study show that the existence of automation is significantly needed to increase the time efficiency of ATC in providing flight information. With automation, the provision of information can be carried out quickly and accurately to increase efficiency and safety in air traffic services. Therefore, this journal provides useful insights into improving the quality of ATC services by utilizing automation technology.